Arthur C. Clarke - Westfahl, Gary (Modern masters of science fiction., 2018)
Despite extensive critical attention, Arthur C. Clarke's distinctive science fiction has never been fully or properly understood. This study examines some of his lighthearted shorter works for the first time and explores how Clarke's views regularly diverge from those of other science fiction writers.